2020
DOI: 10.3126/njh.v17i2.32672
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Extent and Severity of Coronary Artery Disease in Patients with and without Diabetes Mellitus Presenting with Non ST-Segment Elevation Myocardial Infarction

Abstract: Background and Aims: Diabetic patients are at increased risk of developing coronary artery disease. This study was conducted with the aim to compare the extent and severity of coronary artery disease in patients with and without diabetes presenting with non ST segment elevation myocardial infarction (NSTEMI). Methods: This was a single center, hospital based, cross sectional, observational comparative study in which total 172 patients presenting with NSTEMI were divided into two groups of 86 patients eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(26 reference statements)
1
1
0
Order By: Relevance
“…As far as risk factors are concerned, our study found no significant differences regarding previous MI, sex, age, and BMI among both study groups. Although diabetic group had increased number of patients present with dyslipidemia, yet still this was not a statistically significant difference among the two study groups and this finding was in accordance with the findings of the study conducted by Timalsena, et al 19 Nevertheless, diabetic patients present with NSTEMI very noted to have significantly higher rate of smoking. Opposed to our findings, it was shown in a study by Mahadeva, et al 29 that non-diabetic NSTEMI patients have a higher rate of smoking.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As far as risk factors are concerned, our study found no significant differences regarding previous MI, sex, age, and BMI among both study groups. Although diabetic group had increased number of patients present with dyslipidemia, yet still this was not a statistically significant difference among the two study groups and this finding was in accordance with the findings of the study conducted by Timalsena, et al 19 Nevertheless, diabetic patients present with NSTEMI very noted to have significantly higher rate of smoking. Opposed to our findings, it was shown in a study by Mahadeva, et al 29 that non-diabetic NSTEMI patients have a higher rate of smoking.…”
Section: Discussionsupporting
confidence: 88%
“…[12][13][14] It has been demonstrated by the data that CAD is more diffused and severe in patients present with DM in comparison with the patients where DM is absent. 15 A number of studies have been conducted to assess the prognosis and outcome of CAD in diabetic vs non-diabetic patients of acute coronary syndrome 11,16,17 , only a few have focused on severity and pattern of CAD in NSTEMI specifically 18,19 , Furthermore, even though it has been established that CAD is more severe and extensive in the individuals with NSTEMI 15,20,21 , the effect that the status of Diabetes mellitus has on the angiographic profile of the individuals is not currently known so this study provide a piece of evidence about this effect. So this study was performed keeping in mind the aim of comparing severity and extent of the CAD in NSTEMI individuals on the basis of DM.…”
Section: Coronary Artery Diseasementioning
confidence: 99%